Variasi Bahasa Vulgar dalam Film (Pertaruhan) 2017: Kajian Linguistik - Nailatus Saadah; Listiyani Listiyani; Luluatul Maisaroh (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to describe the form of vulgar language variation found in the dialogue of the film betting. Considering that this film is an action film that is popular with teenagers with stories about their lives, the language variation used is interesting to study. This study uses a qualitative descriptive method. Data were obtained from dialogue between characters through the technique of free listening and conversation followed by the technique of taking notes. The results of the study showed 2 data forms of profanity, 9 data forms of curses, and 1 data form of obscenity. These findings indicate that vulgar language in the film betting is not only a form of individual expression, but also reflects complex and conflict-filled social dynamics.